A new species of Caecilia Linnaeus, 1758 (Amphibia: Gymnophiona: Caeciliidae) from the Pacific lowlands of Colombia, with comments on the status of C. tenuissima Taylor, 1973 - Fernández-Roldán, Juan David; Lynch, John D. (Zootaxa, 2023)
We here describe a new species of the genus Caecilia from the Pacific lowlands of Colombia that was mistaken in previous literature as C. tenuissima, but which has more primary and secondary grooves than that species (among other differences). The description of Caecilia wilkinsoni sp. nov. restricts the known distribution of C. tenuissima to Guayaquil, Ecuador, re-establishing its status as an endemic species. We comment on the type locality of C. tenuissima, the current condition of its holotype, and on the distributions of the Caecilia that inhabit the Pacific region of Colombia.